Children’s Headache Through Drawings: A Narrative Review and a Portrait Gallery - Floriana Ferro; Caterina Gaspari; Giulia Manfrè; Federica Cernigliaro; Daniela D’Agnano; Ruben Panzica; Edvige Correnti; Maria Rosita Ruta; Francesca Marchese; Renata Pitino; Mariarita Capizzi; Giuseppe Santangelo; et al. (Life)
Headache represents one of the most prevalent and disabling conditions in the pediatric population, with significant repercussions on mental and psychological well-being, as well as on academic achievement and social functioning, ultimately leading to a marked reduction in quality of life. Currently, the diagnosis of headache is based on the clinical criteria of the third edition of the International Classification of Headache Disorders (ICHD-3). However, the characteristics of headache may differ between adults and children, as well as the ability of children to provide a complete description of the pain and associated symptoms. The immature narrative skills of children can represent a limitation in defining the clinical phenotype of headache, making the diagnosis more complex. This is even more challenging when extracting information about the characteristics of the headache in children whose verbal expression is poorly developed or completely absent. Given these limitations, clinical psychology has long used drawing as an effective diagnostic instrument to bypass verbal communication barriers. This tool provides unique access to children’s psychological and emotional states, as a direct window into their inner world and as an expressive medium that often generates more detailed, accurate, and clinically actionable information, compared to verbal reports alone. For these reasons, drawing has been recognized as a valuable diagnostic tool for decades, with multiple studies demonstrating specificity and accuracy rates comparable to standard clinical assessments. Particularly for young children, drawings may give access to fundamental information that might otherwise remain inaccessible, thereby allowing both accurate diagnosis and individualized treatment planning. Multiple studies have highlighted and confirmed the graphic differences between representations of various types of headaches and the undeniable utility of an “artistic diagnosis” alongside the clinical one. Furthermore, the literature suggests and encourages the use of drawing in clinical practice, both in the diagnostic process and during subsequent follow-up, as an effective, enjoyable, easy-to-use, and low-cost resource. Accordingly, we propose a narrative review accompanied by a curated collection of drawings that may help identify and categorize specific correlations between graphic representations and clinical phenotypes, such as pain location, quality, intensity, association with nausea and vomiting, photophobia and phonophobia, and types of migraine aura. Our goal is to create a visual reference that can aid clinicians in the accurate interpretation of children’s drawings. Additionally, we aim to promote the integration of this method into routine clinical practice to improve diagnostic precision and support a more child-centered model of care. We also hope to propose new iconographic models to further enrich the diagnostic framework.